Effects of Polymer Coated Urea and Irrigation Rates on Lantana Growth and Nitrogen Leaching. Issue 3 (30th June 2017) - Mello, Simone C.; Li, Yuncong C.; Migliaccio, Kati W.; Linares, Eileen P.; Colee, James; Angelotti-Mendonça, Jéssika
Abstract : Core Ideas: Polymer‐coated urea reduced N leaching as compared with conventional urea. Climatic conditions during the lantana growth affected the N uptake and N‐use efficiency. These results can be used for water and fertilizer management for ornamental plants. This study can be used to minimize environmental impact caused by N leaching. Lantana ( Lantana camara L.) is a popular ornamental plant in seaside communities and an annual plant in hanging baskets. This species cultivated as an annual plant in containers needs to receive fertilizers. The nutrient management in containers can be made using conventional or controlled release fertilizers. The effects of ratios among conventional urea (CU) and polymer‐coated urea (PCU), and irrigation water rates applied by evapotranspiration (ET)‐based irrigation were studied on dry weight of biomass and N uptake of lantana, N leaching, water‐use efficiency (WUE), and N‐use efficiency (NUE). Six ratios between CU and PCU (expressed in percentages) and two irrigation rates were evaluated: 0:100, 25:75, 50:50, 75:25, 100:0, and 0:0 of CU/PCU; and water volume applied by 150% of reference evapotranspiration (ETo) and 200% of ETo‐based irrigation. Two trials were conducted with environmental conditions varying between them. With greater temperatures, the cumulative number of inflorescences increased with 100% of PCU as compared with 100% of CU applied in the trial. Polymer‐coated urea (100%) as compared with CU (100%) also reduced N leaching by 64.5 and 61.5% in the first and second trial, respectively. High water volume applied (200% of ETo) increased the dry weight of biomass, N uptake, and NUE. Water volume applied by 150% of ETo‐based irrigation resulted in a reduction of 53.5 and 58.5% of N leaching in the first and second trial, respectively. The response of WUE to ratios among CU and PCU and irrigation rates was not consistent, and was influenced by climatic conditions since WUE increased 26.6% in the second trial characterized for lower temperatures.